1993
DOI: 10.1089/neu.1993.10.25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flunarizine and Methylprednisolone on Functional Recovery After Experimental Spinal Injury*

Abstract: The effect of flunarizine and methylprednisolone on the recovery of somatosensory evoked potentials (SEPs) was evaluated in an experimental model of spinal cord impact injury in anesthetized cats. In addition, the effect of flunarizine on posttraumatic spinal cord blood flow (SCBF) (using the hydrogen clearance technique) and interstitial calcium and potassium activity (ion-selective electrodes) was investigated. After the injury (600 g.cm), SEPs disappeared, followed by a spontaneous recovery to 17% of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This regimen was reported as the optimal dose in cats compared with 15 and 60 mg/kg [70]. The bolus dose of 30 mg/kg plus follow-up administration was also used in experimental SCI of rats [71-73]. In a dose–response study using a ventral compression injury model, the best results were yielded when MPSS was administered in the rats with a bolus dose of 30 mg/kg at 30 min post-SCI followed by a second injection of 15 mg/kg (a total of 45 mg/kg) or with a 60 mg/kg bolus at 30 min post-SCI [74].…”
Section: Discussionmentioning
confidence: 99%
“…This regimen was reported as the optimal dose in cats compared with 15 and 60 mg/kg [70]. The bolus dose of 30 mg/kg plus follow-up administration was also used in experimental SCI of rats [71-73]. In a dose–response study using a ventral compression injury model, the best results were yielded when MPSS was administered in the rats with a bolus dose of 30 mg/kg at 30 min post-SCI followed by a second injection of 15 mg/kg (a total of 45 mg/kg) or with a 60 mg/kg bolus at 30 min post-SCI [74].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of MP have been assessed mostly on motor function (Braughler et al, 1987;Holtz et al, 1990;Means et al, 1981;Rabchevsky et al, 2002), and effects on other important consequences of SCI such as neuropathic pain or autonomic dysfunction have not been emphasized. Some investigators propose to use MP as one of a combination of treatments, as an initial neuroprotective therapy coupled with pro-regenerative or other treatments (Baffour et al, 1995;De Ley et al, 1993;Nash et al, 2002;Takami et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies (24, 25) have reported significant recovery of the somatosensory evoked potentials (SSEPs) by MP, while others have shown no improvement (7-9). Koyanagi and Tator (9) observed that MP did not improve the SSEP, reflecting mainly the dorsal column pathways.…”
Section: Discussionmentioning
confidence: 99%